Speculative attacks: a laboratory study in continuous time - Yin-Wong Cheung; Daniel Friedman (Center for Economic Studies and ifo Institute (CESifo), 2008)
We examine speculative attacks in a controlled laboratory environment featuring continuous time, size asymmetries, and varying amounts of public information. Attacks succeeded in 233 of 344 possible cases. When speculators have symmetric size and access to information: (a) weaker fundamentals increase the likelihood of successful speculative attacks and hasten their onset, and (b) contrary to some theory, success is enhanced by public access to information about either the net speculative position or the fundamentals. The presence of a larger speculator further enhances success, and experience with large speculators increases small speculators' response to the public information. However, giving the large speculator increased size or better information does not significantly strengthen his impact.
Keywords: F30; C73; C92; 330; Currency crisis; speculative attack; laboratory experiment; coordination game; pre-emption; large player; Währungskrise; Devisenspekulation; Test; Spieltheorie